THE INFLUENCE OF THE PROPORTION OF INDEPENDENT COMMISIONERS, MUSLIM DIRECTORS, EXECUTIVE CHARACTER, AND AGE OF THE MAIN DIRECTOR ON TAX AVOIDANCE WITH COMPANY SIZE AS A MODERATIONG VARIABLE (CASE STUDY: COMPANIES REGISTERED AT ISSI IN 2017-2021) - Pratiwii, Intan (Jurnal Al-Iqtishad, 2023)
This study aims to determine the effect of the proportion of Independent Commissioners, Muslim Directors, Management Character, and Age of the Main Director on Tax Avoidance with Company Size as a Moderator in Companies Registered at ISSI in 2017-2021. This research is a quantitative research with secondary data in the form of panel data. The sampling technique is purposive sampling; The sample used is 32 companies registered at ISSI for the 2017-2021 period. The analytical tool used is the Eviews 9 application. The analytical method used is descriptive test, stationarity test, F test, t test, R2 test, classic assumption test, and MRA test. The results showed that the variable proportion of independent commissioners, Muslim directors, and the age of the main director had no effect on tax evasion. Meanwhile, the character of the executive ticket has a significant positive effect on tax evasion. Based on the Moderated Regression Analysis test, it shows that the variable size of the proportion of the company cannot moderate the influence of independent commissioners, Muslim board of directors, executive committee character, and age of the main director on tax avoidance.